Decreased ovarian reserve in HIV-infected women. (24th April 2016) - Santulli, Pietro; de Villardi, Diane; Gayet, Vanessa; Lafay Pillet, Marie-Christine; Marcellin, Louis; Blanchet, Valerie; Gonnot, Julia; Dulioust, Emmanuel; Launay, Odile; Chapron, Charles
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: To evaluate HIV directly or indirectly related altered ovarian function, using serum anti-Müllerian hormone (AMH) levels in HIV-infected women as compared with seronegative women. Design: We conducted a matched cohort study from January 2008 to December 2013 in a tertiary university centre. Two hundred and one HIV-infected women requesting assisted reproductive technology and 603 age and cause of infertility-matched HIV seronegative women were enrolled in this study. Methods: All data were prospectively collected using a semistructured questionnaire. Serum AMH levels in HIV-infected women and matched controls were compared. To find out the contributing factors to increased serum AMH levels in HIV-infected women, a backward multiple linear regression was performed. Results: Serum AMH levels were significantly lower in HIV-infected group as compared with seronegative controls (3.0 ± 2.8 vs 3.7 ± 3.5 ng/ml; respectively, P  = 0.001). Looking for factors associated with altered AMH among HIV-infected women, an association has been shown between tubal disease and a further decrease in serum AMH levels (2.4 ± 2.4 vs 3.4 ± 3.0 ng/ml; respectively, P  = 0.011). Among HIV-infected women, after multivariate linear regression analysis, we showed that increased age, BMI and viral load were associated with decreased serum AMH levels whereas in striking contrast an increase in CD4 + cell count was associated with an increase of serum AMH levels. Conclusion: Serum AMH levels were lower in the HIV-infected group than in the control group. Age, BMI, CD4 + cell count and viral load were the independent contributors affecting serum AMH levels among HIV-infected women.